Sistem Pakar Diagnosa Penyakit Kucing Menggunakan Metode Forward Chaining Berbasis Android - Siti Ayu Latifah (Riset Sinergi Indonesia (RISINDO), 2025)
Cats are among the most popular pets in society due to their friendly and active nature. Scientifically known as Felis Silvestris Catus, cats are one of the most commonly kept pets by humans. In addition to being adorable animals, they are also known for their ability to adapt easily. Cats that are not properly cared for, however, are highly susceptible to various diseases. Diseases in cats are often caused by viruses, parasites, or bacteria that inhabit the cat’s body without the owner’s awareness. Several infectious diseases include Feline Panleukopenia (FPV), Feline Infectious Peritonitis (FIP), Feline Calicivirus (FCV), and Scabies. Meanwhile, non-infectious diseases include Hernia, Abscess, Kidney Failure, and Diabetes Mellitus. From these two categories of diseases, solutions to the problems can be determined by using an expert system. This study aims to develop an Android-based expert system application that can assist cat owners in diagnosing diseases quickly and practically. The method used is forward chaining, as it can trace the symptoms entered by users step by step until reaching a conclusion in the form of a disease diagnosis. The results of the testing show that the application is able to provide diagnoses with a fairly good level of accuracy.